2014
DOI: 10.7589/2013-10-283
|View full text |Cite
|
Sign up to set email alerts
|

Parasitology, Virology, and Serology of Free-Ranging Coyotes (Canis latrans) from Central Georgia, USA

Abstract: ABSTRACT:We examined 31 free-ranging coyotes (Canis latrans) from central Georgia, USA, for select parasites and viral agents. Sixteen coyotes had adult heartworms (Dirofilaria immitis). Serum samples from 27 animals revealed antibodies against canine parvovirus (100%), canine distemper virus (48%), canine adenovirus (37%), and Trypanosoma cruzi (7%); none were detected against Leishmania spp. Twenty-two of 24 (92%) coyotes were positive for Toxoplasma gondii. Real-time PCR of feces revealed 32% of coyotes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 22 publications
5
15
0
Order By: Relevance
“…The 47% heartworm prevalence we detected is similar to values reported in other coyote populations from the region (Holzman et al 1992;Miller et al 2009;Gates et al 2014). However, the antigen test we used could have biased prevalence low if coyotes had male-only heartworm infections or low numbers of female worms.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…The 47% heartworm prevalence we detected is similar to values reported in other coyote populations from the region (Holzman et al 1992;Miller et al 2009;Gates et al 2014). However, the antigen test we used could have biased prevalence low if coyotes had male-only heartworm infections or low numbers of female worms.…”
Section: Discussionsupporting
confidence: 77%
“…The prevalence of antibody to CPV (96%) at Fort Bragg was similar to other studies of coyotes (Holzman et al 1992;Gese et al 1997;Cypher et al 1998;Grinder and Krausman 2001;Gates et al 2014). Our study and several others did not evaluate virus shedding, but Miller et al (2009) reported that one of 36 coyotes in their South Carolina population was shedding based on electron microscopic examination of feces.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations